COMPARATIVE THERMODYNAMIC ANALYSIS OF DUAL CYCLE UNDER ALTERNATIVE CONDITIONS - (:unkn) unknown (VINCA INST NUCLEAR SCI, 2011)
In this paper, finite-time thermodynamic analysis of an air-standard internal-combustion dual cycle is performed. Maximum power. maximum power density, and maximum efficient power, which are three alternative performance criteria, are derived. The effects of the design parameters such as volume ratio and extreme temperature ratio of the cycle have been investigated under maximum power. maximum power density, and maximum efficient power conditions. The analyzed results of air-standard internal-combustion dual cycle showed the design parameters at maximum power conditions and maximum efficient power conditions have a significant advantage compared to maximum power density criterion.
Keywords: finite-time; thermodynamic; heat engine; dual cycle; performance; PERFORMANCE ANALYSIS; PRESSURE RATIO; HEAT-TRANSFER; OPTIMIZATION; ENGINE; POWER; COMBUSTION; EFFICIENCY